The Harmony of Islamic Theology and Kaili Tradition the Perspectives of Muhammadiyah and Nahdlatul Ulama in Local Cultural Policy of Palu City - Sidik Sidik; Surni Kadir; Kamal (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This article discusses the relationship between Islamic theology and the local Kaili tradition in Palu City through the perspective of Indonesia's two largest Islamic organizations, Muhammadiyah and Nahdlatul Ulama (NU). The study focuses on how these two organizations formulate local culture-based policies that maintain harmony between Islamic values and Kaili traditions. The research employs a qualitative approach, utilizing document analysis, in-depth interviews, and participatory observation. The findings reveal that Muhammadiyah and NU have differing yet complementary views on integrating local traditions with Islamic teachings. Muhammadiyah tends to emphasize the purification of faith, while NU is more accommodative of local traditions as long as they do not contradict Islamic law. The cultural policies produced by these organizations in Palu City demonstrate collaborative efforts to preserve the local identity of the Kaili community without neglecting Islamic values. The synergy between these two organizations fosters a productive dialogue space for integrating local traditions with Islamic values, ultimately leading to the creation of inclusive and sustainable cultural policies. This article recommends the importance of cross-organizational collaboration to strengthen local cultural identity within the framework of Islamic theology as a mercy for all creation (rahmatan lil 'alamin). It also underscores the need for ongoing dialogue between religious organizations, local governments, and communities to create inclusive and sustainable cultural policies.